Experimental Study of Spectral Induced Polarization Response Based on Laboratory Measurement - Dicky Ahmad Zaky; Suparwoto Suparwoto (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
The spectral induced polarization (SIP) method can provide apparent complex resistivity based on measurements of multi frequency. SIP method also can provide more detail information about physical properties of rocks and minerals because SIP can give spectral parameters or Cole-Cole parameters such as, changeability (m), time constant (τ) and frequency dependence (c). An Experimental study in laboratory has been conducted to knowing the SIP response of some test sample. The measurement system is built with digital oscilloscope Pico ADC-100 as device for sampling the input and output voltage. Amplifier is used to doubled up the signal and input differential. The range frequency of measurement is 10−2 Hz - 103 Hz. Porouspot Cu − CuSO4 is used to minimize the polarization at potential electrode. A Matlab listings is used to calculate the response of impedance and phase. The result from calibration that used the parallel circuit RC indicate that the measurement system was good. SIP response of porous model indicate that the response form an asymptotic resistivity, and the peak of phase is in the range frequency where the dispersion happen. The result also indicate that resistivity of small grain size model is larger than the big grain size model. Result from sample of mineralized rocks did not indicate a perfect SIP response, it is influenced by the contact between mineral and water was minimum.